THE NECESSITY OF LEARNING ENGLISH FOR TECHNICAL COLLEGE STUDENTS - NEMATOV DAVLATBEK (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In the twenty-first century, English has become the dominant language of science, technology, business, and international communication. For students of technical colleges, proficiency in English is not simply an academic requirement but a professional necessity. A large proportion of scientific publications, technical documentation, international standards, and digital learning platforms operate in English. As a result, students who lack English skills face limitations in accessing updated knowledge, participating in research, and competing in the global labor market. This paper analyzes the necessity of learning English for technical college students. It explores the academic, professional, and social importance of English in technical education. The article also discusses how English proficiency enhances employability, supports international cooperation, and encourages lifelong learning. The study concludes that English should be treated as an essential component of technical training programs.